Biosorpsi Kromium (Cr) Pada Limbah Cair Industri Elektroplating Menggunakan Biomassa Ragi Roti (Saccharomyces cerevisiae) - Resna Rauda Pratiwi; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Electroplating industry is one of industry that produce waste water containing heavy metals. Among the heavy metals contained in the waste water is Chromium (Cr) which have a high toxicity. One technology that can be applied to set aside Cr in wastewater is by biosorption method using biomass derived from baker's yeast (Saccharomyces cerevisiae). This study aimed to study the ability of biomass yeast (Saccharomyces cerevisiae) in designated Cr in weight variation biosorbent is 0.25; 0.5 and 0.75 grams, 80 mesh size; 100 and 140 and the contact time 1; 2; 3 and 4 hours. The results showed the highest removal efficiency of Cr occurs in biosorbent weight of 0.75 grams in a size of 80 mesh and a contact time of 4 hours with an efficiency of 54.7%. Biosorption process showed that values adsorption capacity that is 3.3258 mg Cr / gr biosorbent.Keywords: biosorption, Saccharomyces cerevisiae, Cr, mesh size, contact time, heavy metals